Structure and Backbone Dynamics of Vanadate-Bound PRL-3: Comparison of N-15 Nuclear Magnetic Resonance Relaxation Profiles of Free and Vanadate-Bound PRL-3 - Jeong, Ki-Woong; Kang, Dong-Il; Lee, Eunjung; Shin, Areum; Jin, Bonghwan; Park, Young-Guen; Lee, Chung-Kyoung; Kim, Eun-Hee; Jeon, Young Ho; Kim, Eunice Eunkyeong; Kim, Yangmee (AMER CHEMICAL SOC, 2014)
Phosphatases of regenerating liver (PRLs) constitute a novel class of small, prenylated phosphatases with oncogenic activity. PRL-3 is particularly important in cancer metastasis and represents a potential therapeutic target. The flexibility of the WPD loop as well as the P-loop of protein tyrosine phosphatases is closely related to their catalytic activity. Using nuclear magnetic resonance spectroscopy, we studied the structure of vanadate-bound PRL-3, which was generated by addition of sodium orthovanadate to PRL-3. The WPD loop of free PRL-3 extended outside of the active site, forming an open conformation, whereas that of vanadate-bound PRL-3 was directed into the active site by a large movement, resulting in a closed conformation. We suggest that vanadate binding induced structural changes in the WPD loop, P-loop, helices alpha 4-alpha 6, and the polybasic region. Compared to free PRL-3, vanadate-bound PRL-3 has a longer alpha 4 helix, where the catalytic R110 residue coordinates with vanadate in the active site. In addition, the hydrophobic cavity formed by helices alpha 4-alpha 6 with a depth of 14-15 angstrom can accommodate a farnesyl chain at the truncated prenylation motif of PRL-3, i.e., from R169 to M173. Conformational exchange data suggested that the WPD loop moves between open and closed conformations with a closing rate constant k(close) of 7 s(-1). This intrinsic loop flexibility of PRL-3 may be related to their catalytic rate and may play a role in substrate recognition.
Keywords: PROTEIN-TYROSINE PHOSPHATASES; HEPARIN-BINDING DOMAIN; MODEL-FREE APPROACH; NMR RELAXATION; REGENERATING LIVER; CELL-GROWTH; IDENTIFICATION; METASTASIS; EXPRESSION; MECHANISM